2021
DOI: 10.1097/cm9.0000000000001767
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization followed by surgical resection for hepatocellular carcinoma: a focus on its controversies and screening of patients most likely to benefit

Abstract: Surgical resection (SR) is recommended as a radical procedure in the treatment of hepatocellular carcinoma (HCC). However, postoperative recurrence negatively affects the long-term efficacy of SR, and preoperative adjuvant therapy has therefore become a research hotspot. Some clinicians adopt transcatheter arterial chemoembolization (TACE) as a preoperative adjuvant therapy in patients undergoing SR to increase the resection rate, reduce tumor recurrence, and improve the prognosis. However, the findings of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…TACE is a combination of medical imaging and clinical treatment that has become one of the most important treatments for the treatment of PHC, as it can help reduce tumor volume and allow for a second operation. Although liver resection or transplantation provides better results than other therapies in the local control of HCC, survival rates are unsatisfactory, particularly for large tumors, and it remains controversial whether HCC angiogenesis is enhanced after TACE even in patients undergoing radical resection [ 27 ]. It is frequently utilized in arterial infusion chemotherapy with chemotherapy drugs that are generally given all at once at a high concentration and large dose.…”
Section: Discussionmentioning
confidence: 99%
“…TACE is a combination of medical imaging and clinical treatment that has become one of the most important treatments for the treatment of PHC, as it can help reduce tumor volume and allow for a second operation. Although liver resection or transplantation provides better results than other therapies in the local control of HCC, survival rates are unsatisfactory, particularly for large tumors, and it remains controversial whether HCC angiogenesis is enhanced after TACE even in patients undergoing radical resection [ 27 ]. It is frequently utilized in arterial infusion chemotherapy with chemotherapy drugs that are generally given all at once at a high concentration and large dose.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is controversial whether patients with resectable HCC should receive preoperative TACE preoperatively. Some studies have reported that preoperative TACE has adverse effects, such as perihepatic adhesions that make surgery more difficult, increase the risk of liver injury and liver failure, or delay surgery, thereby allowing continued tumor growth (25)(26)(27). Further, a meta-analysis concluded that HCC patients undergoing hepatectomy do not necessarily derive a survival advantage from preoperative TACE (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the overall cohort, 67.7% of the patients in the high-risk group developed severe PHLF, suggesting stricter standards on the surgical indications, as well as more careful perioperative management. For these patients, it might be safer to choose nonsurgical treatment [ 36 ], neoadjuvant systemic therapy [ 37 ], or TACE followed by hepatectomy [ 38 ]. In comparison with the high-risk group, patients in the low-risk group have a probability of 13.3% for developing PHLF grade B–C, thus considered more appropriate candidates for hepatectomy.…”
Section: Discussionmentioning
confidence: 99%